Os espelhos de Oxum: mulheres periféricas, relações raciais e autoimagem - Silva, Cibele Bitencourt (2020)
The aim of this study is to research the experiences of urban ghetto women who participated in the Sou Minha Project ( I’m Mine Project), and seek to understand the relationships of race, class, gender and territory in the formation of the self-image of urban ghetto women. For this purpose, this study is based on Black and Decolonial Feminist Epistemologies, as well as Critical Social Psychology. In the first chapter, Waters that break the concrete , the historical trajectories and the social constructions that structure us will be discussed. In addition, the notion of coloniality and possible meanings of decolonization will be presented, allowing us to address aspects of African philosophy, concepts of intersectionality and racial relations. In the second chapter, Urban ghetto and urban ghetto women , I discuss about the southern ghetto of the city of São Paulo and contextualize the socio-historical scenario from which this research starts, as well as talk about its protagonists: urban ghetto women. In the third chapter, Mirrors of Oxum (or Osun): photography and self-image , I contextualize the concept of photography and explore the concept of self-image, pointing to teachings of self-knowledge and recognition in the mirror of Oxum. In the fourth chapter, Sou Minha Project and Oxum mirrors , I write about the project's emergence, development and feminist guidelines, as well as address the subjective developments that have occurred in the lives of women who have been photographed, and were able to refuse social impositions of norms and standards regarding beauty. Finally, in Final Reflections in the waters at the end of the course , I reflect on the research path and how the Sou Minha Project reverberated in the lives of the participants. I defend that, in order for us to observe the images in Oxum's mirror, we need time and space so that we can look at ourselves - and get to know who we are. So that, finally, we can recognize ourselves, that is, become familiar with aspects of ourselves. The aim is that we can rupture with determinations imposed by the modern colonial system and its hierarchies of race, gender, class, spirituality and ways of knowing and being